Transcription factors in megakaryocytes and platelets - Yuan, Hengjie; Liu, Yafan; Zhang, Jianning; Dong, Jing-fei; Zhao, Zilong (Frontiers in Immunology, 2023)
Transcription factors bind promoter or regulatory sequences of a gene to regulate its rate of transcription. However, they are also detected in anucleated platelets and increasingly demonstrated to have non-transcriptional activities in platelets. These non-transcriptional activities are independent of gene transcription or protein synthesis and remain poorly defined. The transcription factors RUNX1, GATA1, STAT3, NFB and PPAR have been widely reported to play key roles in the pathophysiology of platelet hyper-reactivity, thrombosis and atherosclerosis. Genetic and acquired defects in these transcription factors are associated with the production of platelet microvesicles that are known to initiate and propagate coagulation and to promote thrombosis. In this review, we summarize recent developments in studying transcription factors in platelet generation, reactivity and production of microvesicles, with focus on non-transcriptional activities of selected transcription factors.